The effects of skewness and kurtosis on production and hedging decisions: a Gram-Charlier expansion approach - Xuejun Jiang; Lingju Cheng; Xinjie Dai (Financial Innovation)
Abstract In this study, we propose a Gram-Charlier expansion approach to investigate the impact of skewness and kurtosis on production and hedging decisions. Consistent with the existing literature, we find that skewness and kurtosis do not affect decisions regarding optimal production; however, they significantly influence optimal hedging decisions. We observe that positive skewness with platykurtic spot prices or negative skewness with leptokurtic spot prices often leads to over-hedging when the initial forward contract price exceeds its expected value. Conversely, under-hedging is expected when the initial forward contract price falls below its expected value. In other conditions, skewness can either promote or impede speculative future trading. Using the Gram-Charlier expansion of the spot price density function, we find that optimal future positions depend on forward prices, the hedgers’ risk preference, and the spot price distribution. Simulations validate our findings on the impact of skewness and kurtosis on future hedging. Finally, we analyze of a cotton storage and forward contracting dataset to illustrate the application of our methodology and support our theoretical results.